Dual-wavelength fiber laser with a bent single-mode multimode single-mode fiber structure - Zulkifli, Ahmad Zarif; Abdul Kadir, N.A.; Ismail, E.I.; Yasin, M.; Jusoh, Z.; Ahmad, Harith; Harun, Sulaiman Wadi (National Institute of Optoelectronics, 2017)
A stable dual-wavelength fiber ring laser operating at C-band region was successfully demonstrated based on a bent singlemode-multimode-single-mode fiber structure (SMS). A small load of 11.34 g is applied at the SMS package to provide bending at the multimode section in order to generate stable dual-wavelength lasing at room temperature. The proposed fiber laser operates at 1535.24 nm and 1540.00 nm with a wavelength spacing of 4.76 nm and a SNR of ∼45 dB. At the pump power of 201 mW, the maximum power fluctuations of ±1.34 dB and ±1.26 dB were obtained at 1535.24 nm and 1540.00 nm respectively. The feasibility of application of SMS structure for dual-wavelength generation is verified.